The immediate effects of whole-body vibration on flexibility and ankle systolic blood pressure in middle-aged individuals with type 2 diabetes mellitus - Khin, May Thandar; Yonglitthipagon, Ponlapat; Sripanya, Peeraphat; Chodnok, Woramate; Wannakarn, Kritnapat; Nakmaroeng, Saowanee; Siritaratiwat, Wantana; Peungsuwan, Punnee; Donpunha, Wanida (Archives of Allied Health Sciences, 2024)
Poor body flexibility in middle-aged individuals with type 2 diabetes mellitus (T2DM) could increase the risk of falls and injuries. Insulin resistance induces vascular alterations in the lower extremities, leading to increased ankle systolic blood pressure (SBP), which correlates with an increased risk of cardiovascular disease. The aim of this study was to investigate the acute effects of whole-body vibration (WBV) on flexibility and ankle SBP in middle-aged T2DM patients. This randomized singleblinded crossover design was used to study 14 participants (average age: 49.71 ± 5.28 years, average body mass index: 26.98 ± 3.24 kg/m2, average duration of diabetes: 2.32 ± 1.74 years) who were randomly assigned to two intervention sequences, starting with non-whole-body vibration (NWBV) or WBV, with seven participants in each sequence. On days 1 and 8, the intervention varied between NWBV and WBV. The outcomes, including flexibility, ankle blood pressure, brachial blood pressure, and the ankle brachial index, were measured at baseline and 15 min, and 45 min after completing the interventions. A repeated measures two-way ANOVA was used for the data analysis. After a 7-day washout period, neither group exhibited a carryover effect. At the post-intervention period, the WBV intervention resulted in a significant increase in flexibility (+3.52 cm after 15 min and +4.20 cm after 45 min; p-value < 0.05) and a significant decrease in ankle SBP (–7.91 mmHg after 15 min; p-value < 0.05) and the ABI (–0.09 after 15 min and –0.07 after 45 min; p-value < 0.05). In contrast, the NWBV intervention led to a significant increase in ankle SBP (+10.50 mmHg after 45 min; p-value < 0.05). These findings show that middle-aged patients with T2DM might benefit from a single session of 12-min WBV training in terms of improving flexibility, ankle SBP, and the ABI. Therefore, it may be an exercise option for middle-aged T2DM patients.